2009
DOI: 10.1128/cvi.00074-09
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Restores Diversity in the T-Cell Receptor Vβ Repertoire of CD4 T-Cell Subpopulations among Human Immunodeficiency Virus Type 1-Infected Children and Adolescents

Abstract: Human immunodeficiency virus (HIV) type 1 infection perturbs the T-cell receptor (TCR) V␤ repertoire.The TCR CDR3 length diversity of individual V␤ families was examined within CD45RA and CD45RO CD4 T cells to assess the impact of the virus on clonality throughout CD4 T-cell activation and differentiation. A cross-sectional and longitudinal cohort study of 13 HIV-infected and 8 age-matched healthy children and adolescents examined the V␤ CDR3 length profiles within CD4 T-cell subsets by the use of spectratypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…[5-7] Our detailed analysis of TCR repertoire substantiates and extends prior studies of HIV-1-infected adults in whom ART does not generally restore CD4 + T-cell numbers to normal or fully normalize skewing of the TCR repertoire, as assessed by various tools ranging from relatively indirect to more precise measures of diversity such as CDR3 size distributions (“spectratyping” or “immunoscoping”), DNA hybridization kinetics (“Amplicot”), multiplex amplification of V-J segments, and CDR3 sequencing,[8, 23, 47-50] and one study in children/adolescents indicating that perturbations in TCR diversity of naïve cells begin to resolve within several months of therapy. [19] Because HIV-1 infection is typically associated with disrupted thymic architecture, involution of the thymic cortical epithelial space, and fibrosis of the peripheral lymph nodes that are required for expansion of thymic emigrants,[41, 51-53] the novel finding of substantially increased TCR breadth in the recent thymic emigrant CD4 + T-cell compartment of our HIV-1-infected subjects was surprising. Supporting this observation, recent trials of administering recombinant human IL-7 to infected persons on ART have demonstrated enhanced naïve CD4 + T-cell production accompanied by indirect measures of increased TCR diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5-7] Our detailed analysis of TCR repertoire substantiates and extends prior studies of HIV-1-infected adults in whom ART does not generally restore CD4 + T-cell numbers to normal or fully normalize skewing of the TCR repertoire, as assessed by various tools ranging from relatively indirect to more precise measures of diversity such as CDR3 size distributions (“spectratyping” or “immunoscoping”), DNA hybridization kinetics (“Amplicot”), multiplex amplification of V-J segments, and CDR3 sequencing,[8, 23, 47-50] and one study in children/adolescents indicating that perturbations in TCR diversity of naïve cells begin to resolve within several months of therapy. [19] Because HIV-1 infection is typically associated with disrupted thymic architecture, involution of the thymic cortical epithelial space, and fibrosis of the peripheral lymph nodes that are required for expansion of thymic emigrants,[41, 51-53] the novel finding of substantially increased TCR breadth in the recent thymic emigrant CD4 + T-cell compartment of our HIV-1-infected subjects was surprising. Supporting this observation, recent trials of administering recombinant human IL-7 to infected persons on ART have demonstrated enhanced naïve CD4 + T-cell production accompanied by indirect measures of increased TCR diversity.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Others have demonstrated that T-cell receptor CDR3 distribution perturbations are rapidly reduced in some children and adolescents during ART [19] suggesting that some degree of normalization of the TCR repertoire is possible. However, these measurements have not excluded qualitative abnormalities in thymopoiesis that might result from the known impact of HIV-1 on the architecture of both the thymus and secondary lymphoid tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on TCR recombination excisional circles (TRECs), a byproduct of TCR rearrangement [26], and phenotypically defined recent thymic emigrants [27] supported thymic output as the driver of immune reconstitution. Using spectratyping methods, the TCR Vβ repertoire complexity was increasing during reconstitution [28] although spectra-type data are not corrected for sample size effects which can be especially important for low CD4 + cell counts, and expansion of individual clones can skew the spectratype and confuse interpretation of data. Sequencing studies are needed to confirm whether reconstitution is associated with increasing TCR repertoire complexity due to new cell synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the rise in the CD4 count results mainly from CD4 + T-cell proliferation and survival, the repertoire will remain uncompleted, even though the total number of CD4 + T-cells has normalized [4143]. …”
Section: How Immune Restoration Can Be Achieved In the Hiv Settingmentioning
confidence: 99%